GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 344537 species occurrences available in GBIF matching the query: TaxonKey: Mammalia Country: Spain HasCoordinate: true HasGeospatialIssue: false. The dataset includes 344537 records from 52 constituent datasets: 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 1 records from Ghent University - Zoology Museum - Vertebrate collection. 204 records from MVZ Mammal Collection (Arctos). 27 records from KUBI Mammalogy Collection. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 90798 records from Inventario Español de Especies Terrestres (MAGRAMA). 1 records from UAM Mammal Collection (Arctos). 122 records from Field Museum of Natural History (Zoology) Mammal Collection. 242 records from iNaturalist Research-grade Observations. 512 records from Mammals housed at MHNG, Geneva. 447 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 88969 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 3 records from Diveboard - Scuba diving citizen science observations. 459 records from naturgucker. 1 records from CAS Mammalogy (MAM). 7 records from UMMZ Mammal Collection. 7 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 124 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 2 records from BioBlitz Barcelona 2010-14. 5 records from LACM Vertebrate Collection. 691 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 3 records from Naturhistorisches Museum Mainz, Zoological Collection. 410 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 1438 records from Institut Mediterrani d'Estudis Avançats: IMEDEA-PALEOVERT. 2 records from Collection Anatomie Histologie - SMF. 4 records from UF Florida Museum of Natural History Mammals. 21696 records from HMAP-History pf Marine Animal Populations (CoML). 24 records from SEAMAP - marine mammals, birds and turtles. 1 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 2016 records from Paleobiology Database. 11 records from Mammal specimens. 8 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 31683 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 200 records from Estacion Biologica Donana - CSIC, Mammal Collection. 37 records from Occurrence of mammalia relicts at site Cueva Millan. 1 records from Herbarium of Umeå University (UME). 22782 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 73474 records from Mammals in MZNA-VERT: pellet sampling. 220 records from Mammals in MZNA-VERT: project Loza. 6 records from UAZ Mammals. 87 records from Geographically tagged INSDC sequences. 2 records from MSB Mammal Collection (Arctos). 201 records from Mammals in MZNA-VERT: project CAS. 4 records from Animal Sound Archive. 15 records from Bat Banding. 2 records from Mammalogy Collection - Royal Ontario Museum. 342 records from Mammals in MZNA-VERT: project Biodiversity of mammals in Pamplona. 2278 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 13 records from Anymals+plants - Citizen Science Data. 2619 records from Data collected on scitizen science web portal www.ornitho.cat. 10 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences